A participação da(o) usuária(o) nos serviços do Centro de Referência de Assistência Social do Município de Poções/BA - Santos, Ângela das Graças Oliveira (2015)
This work comes from the participation of the user in everyday services the Social Assistance Reference Center (Cras) in the city of Poções / BA. Analyzes the socio-historical-cultural context of people accessing the services of Cras, named users and users of the Unified Social Assistance System (Suas), to identify what they think about participation and that participation is this. These thematic guide this work glimpsing possibilities of different forms of participation. It is based on observations, documents and literature surveys and interviews with users , aimed to contribute to the effectiveness of one of the principles of the National Social Assistance Policy (PNAS) related to participation in social control spaces for. advance in social assistance policy. Resulting in an analysis of the understanding of users, the research subjects, in relation to a share linked to the feeling of joy and acceptance, beyond the walls of Cras, which enables service improvements, expansion of rights and overcoming paradigms of social assistance, as concludes. this survey